The Adjustment Potential of Polish Enterprises - Research Results - Sajdak, Maja (Studia Oeconomica Posnaniensia, 2019)
The aim of the article is to identify the adjustment potential of Polish enterprises in terms of their flexibility and the possibility of adapting to an environment and its changes, as well as identifying the relationship between the adjustment potential and the results of business operations. The results of empirical research showing the high adjustment potential in terms of the flexibility of key processes and enterprise resources are presented. The article also discusses correlation relationships between the flexibility of both processes and resources and the results of companies (market and financial).